Genome-Wide Characterization of bHLH Genes in Grape and Analysis of their Potential Relevance to Abiotic Stress Tolerance and Secondary Metabolite Biosynthesis - Wang, Pengfei; Su, Ling; Gao, Huanhuan; Jiang, Xilong; Wu, Xinying; Li, Yi; Zhang, Qianqian; Wang, Yongmei; Ren, Fengshan (Frontiers in Plant Science, 2018)
Abstract Basic helix-loop-helix (bHLH) transcription factors are involved in many abiotic stress responses as well as flavonol and anthocyanin biosynthesis. In grapes (Vitis vinifera L.), flavonols including anthocyanins and condensed tannins are most abundant in the skins of the berries. Flavonols are important phytochemicals for viticulture and enology, but grape bHLH genes have rarely been examined. We identified 94 grape bHLH genes in a genome-wide analysis and performed Nr and GO function analyses for these genes. Phylogenetic analyses placed the genes into 15 clades, with some remaining orphans. 41 duplicate gene pairs were found in the grape bHLH gene family, and all of these duplicate gene pairs underwent purifying selection. Nine triplicate gene groups were found in the grape bHLH gene family and all of these triplicate gene groups underwent purifying selection. Twenty-two grape bHLH genes could be induced by PEG treatment and 17 grape bHLH genes could be induced by cold stress treatment including a homologous form of MYC2, VvbHLH007. Based on the GO or Nr function annotations, we found three other genes that are potentially related to anthocyanin or flavonol biosynthesis: VvbHLH003, VvbHLH007, and VvbHLH010. We also performed a cis-acting regulatory element analysis on some genes involved in flavonoid or anthocyanin biosynthesis and our results showed that most of these gene promoters contained G-box or E-box elements that could be recognized by bHLH family members.